Suicidality in pediatric bipolar disorder: predictor or outcome of family processes and mixed mood presentation? - Algorta, Guillermo Pérez (2011)
OBJECTIVE: Pediatric bipolar disorder (PBD) involves a potent combination of mood dysregulation and interpersonal processes, placing these youth at significantly greater risk of suicide. We examined the relationship between suicidal behavior, mood symptom presentation, family functioning, and quality of life (QoL) in youth with PBD. METHODS: Participants were 138 youths aged 5–18 years presenting to outpatient clinics with DSM-IV diagnoses of bipolar I disorder (n = 27), bipolar II disorder (n = 18), cyclothymic disorder (n = 48), and bipolar disorder not otherwise specified (n = 45). RESULTS: Twenty PBD patients had lifetime suicide attempts, 63 had past or current suicide ideation, and 55 were free of suicide ideation and attempts. Attempters were older than nonattempters. Suicide ideation and attempts were linked to higher depressive symptoms, and rates were even higher in youths meeting criteria for the mixed specifier proposed for DSM-5. Both suicide ideation and attempts were associated with lower youth QoL and poorer family functioning. Parent effects (with suicidality treated as outcome) and child effects (where suicide was the predictor of poor family functioning) showed equally strong evidence in regression models, even after adjusting for demographics. CONCLUSIONS: These findings underscore the strong association between mixed features and suicidality in PBD, as well as the association between QoL, family functioning, and suicidality. It is possible that youths are not just a passive recipient of family processes, and their illness may play an active role in disrupting family functioning. Replication with longitudinal data and qualitative methods should investigate both child and parent effect models.